A comparative weighting analysis using AHP and CRITIC for recycled pavement material selection: A case study from Istanbul - Merve AKBAS; Firat Dogu AKIN (Results in Engineering)
This study presents a dual-phase evaluation of recycled concrete aggregate (RCA) mixtures for pavement base layers, combining laboratory testing and decision analysis. Five RCA–natural aggregate (NA) blends (0 %, 25 %, 50 %, 75 %, and 100 % RCA by weight) were prepared and tested in compliance with Turkish Highways Technical Specifications. All mixtures met required standards for strength and durability. Notably, the 50 % RCA blend achieved a California Bearing Ratio (CBR) of 141 %, while 100 % RCA also met the minimum CBR threshold with a value of 105 %. Environmental indicators improved significantly with RCA use, including a 9.5 kg CO₂/m² reduction in emissions and up to 310 MJ/m² in energy savings at 100 % RCA replacement. To assess broader sustainability, nineteen sub-criteria were weighted under three categories: technical, environmental, and economic. The Analytic Hierarchy Process (AHP) and Criteria Importance Through Intercriteria Correlation (CRITIC) methods were applied independently. AHP prioritized structural strength indicators (e.g., CBR and abrasion resistance), while CRITIC emphasized cost and environmental sub-criteria due to higher variability. The results provide a robust decision-support framework for infrastructure planners and policymakers seeking to optimize RCA use under technical and sustainability constraints. The findings confirm that RCA mixtures, particularly at 50–75 % replacement levels, offer a viable, low-cost, and environmentally beneficial alternative for pavement base applications in urban areas.